PUBLIC SPENDING IN IRAQ AND ITS POSITIVE EFFECTS IN THEE SHORT TERM AT THE MACRO LEVEL - Lafta, Abaas Asfore; Lafta, Abaas Asfore (International Journal of Psychosocial Rehabilitation, 2020)
Iraq’s economic condition is gradually improving following the deep economic strains of the last three years. The defeat of ISIS in end-2017 now leaves the challenging task of rebuilding the infrastructure and providing services and job opportunities to the population. The World Bank estimates the reconstruction cost of at US88 billion postISIS. US30 billion worth of -commitments were made, mostly in the form of loans and guarantees, at the International Conference for the Reconstruction of Iraq, which took place in February 2018 in Kuwait. Reconstruction effort may be delayed due to political uncertainty following elections in May 2018. The rebound of economic growth in 2017 was lower than expected. Iraq maintained oil production in line with the agreement. In 2018, overall GDP growth is estimated to return positive at 1.9 percent thanks to a notable improvement in security conditions, higher oil prices, and expected higher public and private investment. Non-oil growth is estimated to show a strong rebound at 5.2 percent this year, underpinned by broad-based growth in agriculture, industry, and services.